Natural Products for Material Protection: Passivation Enhancing Potentials of Spondias Mombin as AISI 316L Corrosion Inhibitor in 3.5% NaCl Solution (Global Journal of Science Frontier Research, 2019)
The corrosion inhibition characteristics of Spondias mombin (SM) on stainless steel AISI 316L in 3.5% NaCl has been studied using gasometric, potentiodynamic polarization, surface and elemental analysis and computational techniques. Results showed that the inhibition occurs through adsorption of the inhibitor molecules on the metal surface. The effectiveness of protection became more pronounced with decreasing gas evolution as extract concentration increased. Electrochemical results revealed that the extracts’ constituents adsorbed on the AISI 316L surface and enhanced the passivation mechanism which is in agreement with the reduced the anodic and cathodic current densities. Computational simulations were adopted to describe probable reactiveness of SM leaf extract constituents on Fe(110) slab.
Keywords: corrosion inhibition; stainless steel; spondias mombin; elemental analysis; passivation enhancer; adsorption